Sex differences in anxiety, depression, stress and alcohol consumption of university athletes (Impetus, 2026)
University athletes face the challenge of balancing their roles as students and athletes whilst pursuing their education; furthermore, personal factors such as gender and lifestyle choices may affect their performance and well-being. This paper aims to analyze differences by sex regarding stress management, interpersonal relationships, alcohol consumption, anxiety, depression and stress levels in university athletes. A descriptive comparative cross-sectional study of 200 university athletes from a public university in northeastern Mexico. Three questions related to risky drinking from the Alcohol Screening Questionnaire, the depression, anxiety and stress Scale-21 and the interpersonal relationships and stress management subscales from the Health-Promoting Lifestyle Profile-II were used. Statistical analyses were performed using IBM SPSS Statistics (version 25). Differences were found in the levels of depression and stress regarding the frequency of alcohol consumption in the entire sample; an association was found between the presence of depression data and lower levels of lifestyles related to interpersonal relationships and stress management. General trend towards moderation in alcohol consumption. Female university athletes have higher scores in depression, anxiety and stress, presenting a negative association with lifestyle related to stress management compared to their athlete counterparts, although with a positive association regarding interpersonal relationships.
Keywords: Alcohol consumption; Athletes; Healthy lifestyles; Students; Young adults